Kedatangan Tokoh Agama: Berdampak atau Tidak Terhadap Harga Saham - Anindya Salsabilla Zuhroh; Herlinda Maya Kumala Sari; Wisnu Panggah Setiyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine whether the arrival of religious figures: has an impact or not on stock prices, especially on the variables of company growth rate, liquidity and debt to asset ratio (DAR) in infrastructure companies listed on the Indonesian Stock Exchange during the period 2021-2023 and the time period used in the study was 6 months before the arrival of religious figures and 6 months after the arrival of religious figures. researchers used purposive sampling with 22 company samples used. The results of the study showed that the company's growth rate and liquidity did not have a significant effect on prices before or after the arrival of religious figures, while the debt to asset ratio (DAR) had a significant effect on stock prices before and after the arrival of religious figures.